2020
DOI: 10.28991/cej-2020-03091518
|View full text |Cite
|
Sign up to set email alerts
|

Ranking and Determining the Factors Affecting the Road Freight Accidents Model

Abstract: The tremendous growth of population, particularly in developing countries, has led to increased number of travels, especially those with load and freight specifications. Hence, expanding the present facilities or developing new networks or systems concerning freight and transportation is an essential issue. Among the various transportation systems, road freight has secured a significant place in sub-urban transportation, as it is responsible for transporting loads, decreasing transportation costs, and increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was shown that being inattentive to the road ahead and noncompliance with road safety rules were the main variables in road freight collisions. (Bagheri and Shirazian, 2020). Since 'human error' is the main cause of road traffic collisions, there have been attempts to minimize unfavorable driver behaviour in vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that being inattentive to the road ahead and noncompliance with road safety rules were the main variables in road freight collisions. (Bagheri and Shirazian, 2020). Since 'human error' is the main cause of road traffic collisions, there have been attempts to minimize unfavorable driver behaviour in vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that in accordance with the accident severity model in 2016, Several factors such as the season of autumn, daytime light, drivers aged from 18 to 60, and pickup trucks have impacted the on-road freight accident severity. While, in 2017 the severity was affected by factors like rural road, freight trucks, non-faulty passenger cars, motorcycles, and pedestrians [27]. With the above information and data assessment, very little study has been carried out yet in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…The timing (e.g. flexible working hours vs. morning rush hour trips (Shove, 2002) may influence mode choice from a reliability perspective, and daytime/nighttime travel and lighting also has an impact on accident rates, which may in turn influence the psychosocial attitudes towards the safety of a mode (Ramiani and Shirazian, 2020;Uttley et al, 2020). Depending on location, warmer weather may increase active travel (Børrestad et al, 2011), or conversely, decrease it (Wang et al, 2020), although adverse conditions tend to decrease active travel in general.…”
Section: The Meso Levelmentioning
confidence: 99%